2006
DOI: 10.1080/09513590600762265
|View full text |Cite
|
Sign up to set email alerts
|

Hypoactive sexual desire disorder in postmenopausal women

Abstract: Decreases in sex hormone levels with menopause may bring about a number of consequences in women's general health and sexual well-being, especially when levels decline suddenly and prematurely, as in surgical menopause. In addition to the well-established role of estrogens in preserving the biological basis of sexual response, there is emerging evidence that androgens are significant independent determinants affecting sexual desire, activity and satisfaction, as well as mood, energy and other components of wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 45 publications
1
14
0
6
Order By: Relevance
“…HSDD correlates with low feelings of physical and emotional satisfaction, poor self-image, and unhappiness [25]. Research suggests multiple psychological reasons why women choose to engage in sexual activity, including wanting to feel close to a partner, expression of love, and wanting to feel feminine[26].…”
Section: Hypoactive Sexual Desire Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…HSDD correlates with low feelings of physical and emotional satisfaction, poor self-image, and unhappiness [25]. Research suggests multiple psychological reasons why women choose to engage in sexual activity, including wanting to feel close to a partner, expression of love, and wanting to feel feminine[26].…”
Section: Hypoactive Sexual Desire Disordermentioning
confidence: 99%
“…The role of hormone therapy in consistently increasing sexual desire or activity has not been established [25]. Sexual activity analysis from the Women’s Health Initiative found no statistically significant correlation between use of hormone therapy and the continuation of sexual activity, further supporting that estrogen therapy does not increase libido [46].…”
Section: Treatmentsmentioning
confidence: 99%
“…Therefore, even though psychorelational issues and sociocultural factors should always be ruled out, there is no doubt that biological aspects, including sex hormone deficiency, as well as other medical conditions and medications which may cause a neuroendocrine imbalance, play a major role in the clinical manifestation of sexual problems that induce personal distress and, therefore, may require intervention 26,27. Indeed, the iatrogenic removal of both ovaries, which may occur well before the age of natural menopause, is characterized by the effects of acute estrogen and even androgen deprivation in several domains of sexual function (desire, arousal, lubrication, orgasm, satisfaction) and has been significantly associated with HSDD and severity of other menopausal symptoms such as vaginal dryness 2830. Following bilateral oophorectomy, both premenopausally and postmenopausally, there is a sudden 50% fall in circulating testosterone (T) levels which have been associated with the so-called androgen-insufficiency syndrome; an increasingly accepted clinical entity comprising specific symptoms such as low sexual desire, persistent and inexplicable fatigue, blunted motivation and a general reduced sense of well-being 31.…”
Section: Contributors To Hsddmentioning
confidence: 99%
“…Surgical menopause has long been significantly associated with the occurrence of sexual symptoms, mainly vaginal dryness and the decline or loss of libido/sexual desire 1,2 . A number of observational studies, both cross-sectional and longitudinal, have suggested that bilateral oophorectomy has a greater negative impact on sexual functioning than hysterectomy alone [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%